Dampak Oligopoli Terhadap Ekonomi Masyarakat Di Wilayah Surabaya - Muhammad Yasin; Hendrik Hermansyah; Yeny Novita Fitriani; Dhaful Oktaviatul (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Oligopoly is a form of market structure where there are a few producers or dominate the market for a particular product or service. In an oligopoly, there are a few large companies that control most of the supply of goods or services, thus having the ability to influence prices and control competition. In an oligopoly market, each company will position itself as part of the market game. This certainly needs to be done because the profits they get are very dependent on their competing companies. Every policy taken by one company will greatly influence other companies so that competition will become increasingly fierce in terms of price and quality.